A dual-biomass porous carbon material and its preparation method and application
By using reed straw and tannin as bicarbonate sources, combining potassium hydroxide and melamine, the lack of mesoporous and macroporous structures in biomass carbon materials is solved. The problem of high-performance supercapacitor electrode material is achieved, suitable for commercial production and cycle stability.
Patent Information
- Application Number
- CN202410153287.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-02
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-02-02
AI Technical Summary
The existing biomass carbon materials lack mesoporous and macroporous structures in supercapacitors, and some material elements are single, making it difficult to achieve abundant heteroatom doping, which limits its electrochemical properties.
Reed straw and tannin acid as bicarbonate sources, combined with potassium hydroxide and melamine, and in situ synthesize nitrogen and oxygen-co-doped bibiomass honeycomb-like porous carbon materials through chemical activation to form both micropores and mesoporous Graded three-dimensional structure.
The activity and electrochemical properties of the supercapacitor electrode are improved, and the material has a high specific surface area and excellent conductivity, which is suitable for commercial production, and has good cycle stability.
Smart Images

Figure CN117985713B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrode materials, and in particular relates to a dual-biomass porous carbon material and a preparation method and application thereof. Background Art
[0002] Innovation and continuous progress in the energy field have brought new strategic opportunities and challenges to the storage and conversion of energy in electrochemical devices such as batteries and supercapacitors. As a member of the energy storage system, supercapacitors (SCs) have attracted much attention due to their good cycle stability, high power density, wide operating temperature and fast charging and discharging. From the defense industry to new energy vehicles, from urban public transportation to smart grids, from flexible wearable devices to new smart packaging, SCs have made significant contributions as an instantaneous power output appliance. Today, the global supercapacitor market is still growing, and my country's supercapacitor industry will continue to maintain a high growth trend.
[0003] Currently, many materials are used to construct electrodes for supercapacitors, such as transition metal oxides, conductive polymers, carbon materials, etc. Common carbon materials include biomass, carbon fiber, carbon aerogel, carbon nanotubes, graphene, etc. For carbon fiber, graphene, carbon aerogel and carbon nanotubes, their commercialization is limited due to their high cost, non-renewable nature and complex synthesis process.
[0004] Biomass has a natural multi-level porous structure, which makes the synthesis of biomass carbon safer and more environmentally friendly than other carbon materials. In addition, as a green raw material, biomass has the characteristics of rich variety, renewable, low cost and its own unique three-dimensional intrinsic morphology. It is an ideal natural resource for preparing supercapacitor electrode materials and has attracted widespread attention from researchers in recent years. Carbon materials derived from biomass have the following advantages: (1) They are rich in carbon elements and have a high carbon yield; (2) Their own special morphology and structure are retained during high-temperature carbonization, and they have excellent specific surface area and developed pore structure, which can promote the rapid transmission of ions and improve rate performance; (3) They contain elements such as N, O, P, S, and B, which can increase surface wettability and induce the formation of additional electrochemical active sites to increase the total capacitance. Based on the above advantages, using biomass as a raw material in supercapacitors to construct three-dimensional porous carbon materials with high specific surface area, high conductivity and heteroatom doping can achieve excellent electrochemical performance. However, there are many types of biomass carbon materials, and there are still some problems in using them as electrode materials for supercapacitors: (1) Traditional biomass carbon materials have a relatively developed microporous structure, but their lack of mesoporous and macroporous structures affects their application in supercapacitors; (2) The elemental composition of some agricultural and forestry waste biomass materials is too simple, mainly C, H, and O elements, with very little heteroatom content. Therefore, how to achieve rich heteroatom doping has become the key direction for preparing efficient biomass-based electrode materials; (3) Some biomass does not have a unique morphology, and how to give these biomass materials a special structural morphology through appropriate means is also a difficult problem to overcome. Therefore, it is urgent to prepare biomass carbon materials with a hierarchical porous structure and high specific capacitance. Summary of the invention
[0005] In view of the above problems existing in existing biomass carbon materials, the present invention provides a dual-biomass porous carbon material and a preparation method and application thereof. The present invention uses reed straw and tannic acid (TA) as dual carbon sources, potassium hydroxide and nitrogen source melamine for joint activation, and in-situ synthesizes nitrogen and oxygen co-doped dual-biomass honeycomb porous carbon materials (N-RTC) with ultra-high specific surface area. The dual-biomass porous carbon material is used to prepare electrodes, thereby improving the activity of supercapacitor electrodes and the electrochemical performance of supercapacitors. Biomass raw materials are easy to obtain, the preparation process is simple and environmentally friendly, and it is conducive to large-scale production and suitable for commercialization.
[0006] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a dual-biomass porous carbon material, comprising: a dual-biomass carbon source, an activator and a nitrogen source, which is synthesized in situ with the dual-biomass carbon source as a matrix under the synergistic action of the activator and the nitrogen source; the dual-biomass carbon source comprises reed straw and tannic acid, the activator comprises potassium hydroxide, and the nitrogen source comprises melamine.
[0008] Compared with the prior art, the dual-biomass porous carbon material of the present invention has at least the following beneficial effects: reed and tannic acid are both abundant biomass resources, among which reed is used for wetland protection and is distributed in many areas on the earth. Reed straw, as an important component of reed, mainly includes various components such as carbohydrates, proteins, cellulose, vitamins and minerals. Tannic acid is a naturally abundant polyphenol substance that can be extracted from many plants. Reed straw and tannic acid are used as biomass raw materials, which are easy to obtain, low in cost, green and environmentally friendly, and are very suitable precursors for synthetic carbon materials.
[0009] The carbon material obtained by using reed straw as a single carbon source maintains the hollow tubular shape of the reed straw while forming some rough pores on the surface. After adding a nitrogen source, more dense microporous structures are formed on the surface of the reed straw. The present invention uses reed straw and tannic acid as dual biomass carbon sources, KOH as an activator, and melamine as a nitrogen source and a pore modifier at the same time. Under the synergistic effect of the activator, the pore modifier and the nitrogen source, the hollow tubular structure of the reed straw itself disappears, and the in-situ loaded synthesis of dual biomass-derived nitrogen and oxygen co-doped honeycomb graded porous carbon material is prepared. This carbon material with a unique structure has a very high specific surface area. The pore utilization rate can be improved to obtain higher capacitance characteristics. In addition, by adding a nitrogen source to form a nitrogen and oxygen co-doped structure, not only the conductivity and hydrophilic polarization sites can be improved, but also the pseudocapacitance and energy density of the porous carbon material can be improved through redox reactions.
[0010] In one embodiment, the dual biomass porous carbon material is a hierarchical three-dimensional honeycomb structure with both micropores and mesopores, the pore size of the micropores is less than 2nm, the pore size of the mesopores is 2nm to 50nm, the proportion of the micropores and mesopores to all pores is 85% to 95%, and the pore volume is 0.90cm 3 g -1 ~1.30cm 3 g -1 , with a specific surface area of 1900m 2 g -1 ~2600m 2 g -1 The nitrogen doping atomic ratio is 2% to 6%, and the oxygen doping atomic ratio is 12% to 16%.
[0011] The dual-biomass porous carbon material of the present invention has both micropores and mesopores, and has a high specific surface area and pore volume. The large specific surface area and layered porous structure provide more active sites and smooth channels for rapid ion transfer, while the abundant N and O functional groups improve the electronic conductivity, wettability between the electrode and the electrolyte, and pseudocapacitance performance, which is beneficial to improving its electrochemical properties as an electrode material.
[0012] In one of the embodiments, the mass ratio of the dual biomass carbon source, nitrogen source and activator is 1:1:2.5 to 1:2:3.5.
[0013] In the experimental exploration, the inventors tried to regulate the ratio of the dual biomass carbon source, the nitrogen source and the activator KOH many times, in order to find a hierarchical three-dimensional honeycomb structure with both micropores and mesopores, and a carbon material with a high specific surface area. When the two biomass carbon sources are mixed and the nitrogen source is introduced (the mass ratio of the dual biomass carbon source to the nitrogen source is 1:1), the obtained carbon material presents an interconnected porous structure; when the amount of the nitrogen source is further increased, the micropores and mesopores continue to increase. However, as the nitrogen doping ratio increases, when the mass ratio of the dual biomass carbon source to the nitrogen source exceeds 1:2, the pores begin to agglomerate into clumps and are uneven. Finally, the above-mentioned optimized ratio is obtained. .
[0014] In a second aspect, the present invention provides a method for preparing the above-mentioned dual biomass porous carbon material, comprising the following steps:
[0015] S1: heating reed straw and tannic acid for pre-carbonization and cooling them to obtain pre-carbonized reed straw and pre-carbonized tannic acid;
[0016] S2: mixing the pre-carbonized reed straw, pre-carbonized tannic acid and melamine and grinding them uniformly to obtain a mixed precursor, mixing the mixed precursor with KOH, adding an appropriate amount of deionized water for impregnation, stirring, and drying to obtain a calcined precursor;
[0017] S3: calcining the calcined precursor at a high temperature in an inert atmosphere to obtain a calcined product, wherein the calcination temperature is 600° C. to 800° C.;
[0018] S4: acid-washing the calcined product to obtain an acid-washed product;
[0019] S5: The acid-washed product is filtered, washed with deionized water until neutral, and dried to obtain the dual-biomass porous carbon material.
[0020] The present invention uses reed straw and tannic acid as dual biomass carbon sources, and uses chemical activation to convert dense materials into porous materials through a simple process of pre-carbonization-impregnation-high-temperature calcination. First, the dual biomass carbon source is pre-carbonized, and the pre-carbonized product is mixed with a nitrogen source and a KOH activator. After impregnation, high-temperature calcination is performed. The activator penetrates into the structure of the pre-carbonized product, so that the activated pre-carbonized product grows a microscopic pore structure. At 600°C to 800°C, the nitrogen source is rapidly decomposed into nitrogen-containing substances, such as NH3, C2N2 + 、C3N2 + and C3N3 + Under the synergistic effect of nitrogen source and KOH, the dual-biomass carbon material can be etched to form a nitrogen- and oxygen-co-doped honeycomb porous structure. This unique structure gives the carbon material a high specific surface area, exposing more active sites, thereby improving the activity of the supercapacitor. The preparation method is simple, and the obtained electrode material has a unique structure, which has broad application prospects in the field of energy storage and conversion.
[0021] In one embodiment, before step S1, the reed straw is pre-treated by washing, drying, crushing and screening.
[0022] The reed straw is subjected to the pretreatment steps of washing, drying, crushing and sieving to obtain reed straw powder with small particles, which is beneficial to the subsequent treatment steps.
[0023] In one of the embodiments, in step S1, the heating rate of the heating process is 4°C / min to 6°C / min, the pre-carbonization temperature is 400°C to 600°C, and the pre-carbonization time is 0.5h to 1.5h.
[0024] Preferably, in step S1, the heating rate of the heating process is 5°C / min, the pre-carbonization temperature is 500°C, and the pre-carbonization time is 1 hour.
[0025] The optimal heating rate, pre-carbonization temperature and time can ensure a steady increase in temperature, fully pre-carbonize the dual biomass carbon source, enhance the stability of the pre-carbonization product, and ensure that subsequent impregnation and high-temperature calcination proceed smoothly.
[0026] In one embodiment, in step S2, the mass ratio of the pre-carbonized reed straw to the pre-carbonized tannic acid is 1:0.5 to 1:1.5, preferably, the mass ratio is 1:1.
[0027] In one embodiment, in step S2, the mass ratio of the total mass of the pre-carbonized reed straw and the pre-carbonized tannic acid, the nitrogen source and the KOH is 1:1:2.5 to 1:2:3.5. Preferably, the mass ratio is 1:1.5:3.
[0028] In the experimental exploration, the inventors tried many times to regulate the ratio of the dual biomass carbon source, nitrogen source and KOH, in order to find a hierarchical three-dimensional honeycomb structure with both micropores and mesopores, and a carbon material with a high specific surface area. When the two biomass carbon sources are mixed and the nitrogen source is introduced (the mass ratio of the dual biomass carbon source to the nitrogen source is 1:1), the obtained carbon material presents an interconnected porous structure; when the amount of the nitrogen source is further increased, the micropores and mesopores continue to increase. However, as the nitrogen doping ratio increases, when the mass ratio of the dual biomass carbon source to the nitrogen source exceeds 1:2, the pores begin to agglomerate into clumps and are uneven. Finally, the above-mentioned optimized ratio is obtained.
[0029] In one embodiment, in step S2, the volume of the deionized water is 20 mL to 30 mL, the stirring time is 11 h to 13 h, the drying temperature is 80° C. to 100° C., and the drying methods include forced air drying and vacuum drying.
[0030] In one embodiment, in step S3, the heating rate is 4°C / min to 6°C / min, and the insulation time is 0.5h to 1.5h.
[0031] Preferably, in step S3, the heating rate is 5°C / min, the calcination temperature is 700°C, and the holding time is 1h.
[0032] In step 3, the high-temperature calcination temperature is 600°C to 800°C. If the temperature is too low, a special honeycomb structure cannot be constructed and the nitrogen doping effect is not obvious. If the temperature is too high, the corresponding honeycomb structure will collapse and a carbon material with both micropores and mesopores cannot be obtained.
[0033] In one embodiment, in step S4, the pickling agent used for pickling is HCl solution with a concentration of 1 moL / L to 3 moL / L, and the pickling time is 8 h to 12 h.
[0034] If other acidic substances such as H2SO4 and HNO3 solutions are used for cleaning, other impurities will be further introduced, increasing the difficulty of post-processing, so HCl solution is used as the pickling agent.
[0035] In a third aspect, the present invention provides a use of the dual-biomass porous carbon material described in the first aspect or the dual-biomass porous carbon material obtained by the preparation method described in the second aspect in the preparation of supercapacitor electrode materials.
[0036] The dual-biomass porous carbon material prepared by the present invention has good application prospects in supercapacitors. Compared with electrode materials such as transition metal oxides and conductive polymers, the raw material cost is low and the source is abundant, the preparation process is simple, and it is conducive to large-scale production.
[0037] According to the energy storage mechanism, the specific surface area, pore structure, surface functional groups and conductivity of carbon materials are key factors affecting the energy storage of supercapacitors. The dual-biomass porous carbon material prepared by the present invention has a high specific surface area and excellent double-layer capacitance characteristics, as well as pseudocapacitance characteristics generated by the redox reaction of N and O functional groups, and has a strong adsorption / desorption ability for electrolyte ions, thereby enhancing the capacitance. In addition, it has a fast current response speed. The maximum energy density is as high as 18.32Wh / kg, the maximum power density is 5000W / kg, and after 10,000 charge and discharge cycles, the capacitance retention rate can reach up to 96%, with good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 In the figure, (a)-(f) are SEM images of samples prepared in comparative examples and embodiments of the present invention, respectively.
[0039] Figure 2 In the figure, (a) is a N2 adsorption-desorption curve diagram of the samples prepared in the embodiments of the present invention and the comparative examples, and (b) is a pore size distribution curve diagram.
[0040] Figure 3 In the figure, (a) is the cyclic voltammetric characteristic curve (CV) of the samples prepared in the embodiments of the present invention and the comparative examples at a scanning rate of 100 mV / s, and (b) is the constant current charge-discharge curve (GCD) at a current density of 1 A / g.
[0041] Figure 4 In the figure, (a) is the CV curve of the symmetrical supercapacitor device at a scan rate of 5mV / s to 100mV / s, (b) is the GCD curve of the symmetrical supercapacitor device at a current density of 0.5A / g to 10A / g, (c) is the energy density and power density diagram of the N-RTC-1.5 / / N-RTC-1.5 symmetrical supercapacitor, and (d) is the cycle performance test diagram of the N-RTC-1.5 electrode at a current density of 3A / g. DETAILED DESCRIPTION
[0042] The present invention is further described below in conjunction with specific embodiments. It should be noted that the following embodiments are only used to illustrate the present invention rather than to limit the technical solutions described in the present invention, and all technical solutions and improvements that do not depart from the present invention should be included in the scope of the claims of the present invention.
[0043] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the invention, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of the present invention, the meaning of "several" is at least one, such as one, two, etc., unless otherwise clearly and specifically defined.
[0044] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.
[0045] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0046] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0047] The following are specific examples. Unless otherwise specified, the raw materials used in the examples are all commercially available products.
[0048] The embodiment of the present invention provides a dual-biomass porous carbon material and a preparation method and application thereof. The carbon material uses reed straw and tannic acid as biomass precursors, and uses nitrogen source melamine and KOH to in-situ load and synthesize a dual-biomass derived nitrogen and oxygen co-doped honeycomb hierarchical porous structure, which can be used to prepare electrode materials for supercapacitors. The specific preparation process is as follows:
[0049] S1: Reed straw (RS) and tannic acid (TA) are placed in a quartz boat respectively, heated to 400°C to 600°C at a heating rate of 4°C / min to 6°C / min in a nitrogen atmosphere, pre-carbonized for 0.5h to 1.5h, and cooled to obtain pre-carbonized reed straw and pre-carbonized tannic acid;
[0050] S2: Pre-carbonized reed straw and pre-carbonized tannic acid are placed in an agate mortar at a mass ratio of 1:0.5 to 1:1.5, and nitrogen source melamine is added in a ratio of 1:1 to 1:2 to the mass ratio of carbon source to nitrogen source. The carbon source and the nitrogen source are evenly ground to fully mix to obtain a mixed precursor. The mixed precursor and KOH are mixed and placed in a beaker with a mass ratio of carbon source to KOH of 1:2.5 to 1:3.5, and 20 mL to 30 mL of deionized water are added for immersion and stirring for 11 h to 13 h, followed by drying at 80 ° C to 100 ° C to obtain a calcined precursor.
[0051] S3: placing the calcined precursor in a tube furnace, heating it to 600°C to 800°C at a heating rate of 4°C / min to 6°C / min in an inert atmosphere, and keeping the temperature for 0.5h to 1.5h to obtain a calcined product;
[0052] S4: acid-washing the calcined product in a 1 mol / L to 3 mol / L HCl solution for 8 to 12 hours until the KOH and other impurities remaining on the surface of the material are washed away to obtain an acid-washed product;
[0053] S5: The acid-washed product is filtered, washed with deionized water until neutral, and dried to obtain the dual biomass porous carbon material N-RTC.
[0054] The prepared dual-biomass porous carbon material N-RTC has a hierarchical three-dimensional honeycomb structure with both micropores and mesopores. The pore size of the micropores is less than 2nm, the pore size of the mesopores is 2nm to 50nm, the proportion of micropores and mesopores in all pores is 85% to 95%, and the pore volume is 0.90cm 3 g -1 ~1.30cm 3 g -1 , with a specific surface area of 1900m 2 g -1 ~2600m 2 g -1 The nitrogen doping atomic ratio is 2% to 6%, and the oxygen doping atomic ratio is 12% to 16%.
[0055] Example 1
[0056] A method for preparing a dual biomass porous carbon material comprises the following steps:
[0057] S1: Reed straw (RS) and tannic acid (TA) were placed in a quartz boat, heated to 400°C at a heating rate of 4°C / min in a nitrogen atmosphere, pre-carbonized for 1.5 h, and cooled to obtain pre-carbonized reed straw and pre-carbonized tannic acid;
[0058] S2: Weigh 0.15 g of pre-carbonized reed straw and 0.15 g of pre-carbonized tannic acid and place them in an agate mortar, add 0.3 g of melamine, grind evenly to fully mix the carbon source and the nitrogen source to obtain a mixed precursor, place the mixed precursor in a beaker, add 0.75 g of KOH and 20 mL of deionized water, soak and stir for 11 h, and then dry with air at 80 ° C to obtain a calcined precursor;
[0059] S3: placing the calcined precursor in a tube furnace, heating to 600°C at a heating rate of 4°C / min under a nitrogen atmosphere, and keeping the temperature for 1.5 h to obtain a calcined product;
[0060] S4: The calcined product is acid-washed in a 1 mol / L HCl solution for 10 h until the KOH and other impurities remaining on the surface of the material are washed away to obtain an acid-washed product;
[0061] S5: The acid-washed product was filtered, washed with deionized water until neutral, and vacuum dried to obtain the dual-biomass porous carbon material N-RTC-1, with a nitrogen-doped atomic ratio of 2.38% and an oxygen-doped atomic ratio of 12.69%.
[0062] Example 2
[0063] A method for preparing a dual biomass porous carbon material comprises the following steps:
[0064] S1: Reed straw (RS) and tannic acid (TA) were placed in a quartz boat, respectively, heated to 500°C at a heating rate of 5°C / min in a nitrogen atmosphere, pre-carbonized for 1.0 h, and cooled to obtain pre-carbonized reed straw and pre-carbonized tannic acid;
[0065] S2: Weigh 0.15 g of pre-carbonized reed straw and 0.15 g of pre-carbonized tannic acid and place them in an agate mortar, add 0.45 g of melamine, grind evenly to fully mix the carbon source and the nitrogen source to obtain a mixed precursor, place the mixed precursor in a beaker, add 0.9 g of KOH and 25 mL of deionized water, soak and stir for 12 h, and then dry with air at 100 ° C to obtain a calcined precursor;
[0066] S3: placing the calcined precursor in a tube furnace, heating to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere, and keeping the temperature for 1.0 h to obtain a calcined product;
[0067] S4: The calcined product is pickled in a 3 mol / L HCl solution for 8 h until the KOH and other impurities remaining on the surface of the material are washed away to obtain an acid-washed product;
[0068] S5: The acid-washed product was filtered, washed with deionized water until neutral, and vacuum dried to obtain the dual-biomass porous carbon material N-RTC-1.5, with a nitrogen-doped atomic ratio of 3.56% and an oxygen-doped atomic ratio of 13.70%.
[0069] Example 3
[0070] A method for preparing a dual biomass porous carbon material comprises the following steps:
[0071] S1: Reed straw (RS) and tannic acid (TA) were placed in a quartz boat, heated to 600°C at a heating rate of 6°C / min in a nitrogen atmosphere, pre-carbonized for 0.5h, and cooled to obtain pre-carbonized reed straw and pre-carbonized tannic acid;
[0072] S2: Weigh 0.15 g of pre-carbonized reed straw and 0.15 g of pre-carbonized tannic acid and place them in an agate mortar, add 0.60 g of melamine, grind evenly to fully mix the carbon source and the nitrogen source to obtain a mixed precursor, place the mixed precursor in a beaker, add 1.0 g of KOH and 30 mL of deionized water, soak and stir for 13 h, and then dry with air at 100 ° C to obtain a calcined precursor;
[0073] S3: placing the calcined precursor in a tube furnace, heating to 800°C at a heating rate of 6°C / min under a nitrogen atmosphere, and keeping the temperature for 0.5h to obtain a calcined product;
[0074] S4: The calcined product is acid-washed in a 2 mol / L HCl solution for 12 h until the KOH and other impurities remaining on the surface of the material are washed away to obtain an acid-washed product;
[0075] S5: The acid-washed product was filtered, washed with deionized water until neutral, and vacuum dried to obtain the dual-biomass porous carbon material N-RTC-2, with a nitrogen-doped atomic ratio of 5.62% and an oxygen-doped atomic ratio of 15.36%.
[0076] Comparative Example 1
[0077] A method for preparing a carbon material comprises the following steps:
[0078] S1: Reed straw (RS) was placed in a quartz boat, heated to 500°C at a heating rate of 5°C / min in a nitrogen atmosphere, pre-carbonized for 1.0 h, and cooled to obtain pre-carbonized reed straw;
[0079] S2: Weigh 0.3 g of pre-carbonized reed straw and place it in an agate mortar, grind it evenly and thoroughly, place it in a beaker after grinding, add 0.9 g of KOH and 25 mL of deionized water, soak and stir for 12 h, then air dry it at 100 ° C to evaporate the water to obtain a calcined precursor;
[0080] S3 to S5 are the same as in Example 2, and a carbon material RSPC is obtained, wherein the nitrogen-doped atomic ratio is 0.92% and the oxygen-doped atomic ratio is 13.36%.
[0081] Comparative Example 2
[0082] A method for preparing a carbon material comprises the following steps:
[0083] S1: Reed straw (RS) was placed in a quartz boat, heated to 500°C at a heating rate of 5°C / min in a nitrogen atmosphere, pre-carbonized for 1.0 h, and cooled to obtain pre-carbonized reed straw;
[0084] S2: Weigh 0.3 g of pre-carbonized reed straw and place it in an agate mortar, add 0.45 g of melamine, grind it evenly to fully mix the carbon source and the nitrogen source, place it in a beaker after grinding, add 0.9 g of KOH and 25 mL of deionized water, soak and stir for 12 h, then dry it with air at 100 ° C to evaporate the water to obtain a calcined precursor;
[0085] S3 to S5 are the same as in Example 2, and a carbon material N-RSPC is obtained, wherein the nitrogen-doped atomic ratio is 4.35% and the oxygen-doped atomic ratio is 15.12%.
[0086] Comparative Example 3
[0087] A method for preparing a carbon material comprises the following steps:
[0088] S1: placing tannic acid (TA) in a quartz boat, heating to 500°C at a heating rate of 5°C / min in a nitrogen atmosphere, pre-carbonizing for 1.0 h, and cooling to obtain pre-carbonized tannic acid;
[0089] S2: Weigh 0.3 g of pre-carbonized tannic acid and place it in an agate mortar, grind it evenly and thoroughly, place it in a beaker after grinding, add 0.9 g of KOH and 25 mL of deionized water, soak and stir for 12 h, then blow dry at 100 ° C to evaporate the water to obtain a calcined precursor;
[0090] S3 to S5 are the same as in Example 2, and a carbon material TAC is obtained, wherein the nitrogen doping atomic ratio is 0 and the oxygen doping atomic ratio is 10.13%.
[0091] Test example
[0092] The samples prepared in all the embodiments and comparative examples of the present invention were analyzed by scanning electron microscope. Figure 1The SEM images of all samples prepared in the embodiments of the present invention and the comparative examples are shown in Figure 2. After the pre-carbonized reed straw is directly activated and carbonized, the obtained sample RSPC maintains the hollow tubular shape of the reed straw while forming some rough pores on the surface, such as Figure 1 (a) As shown; after nitrogen doping, due to the synergistic effect of KOH and nitrogen source, more dense microporous structures are formed on the surface of reed straw in the obtained sample N-RSPC, such as Figure 1 (b) As shown; after direct activation and carbonization of pre-carbonized tannic acid, the obtained sample TAC has a thin-walled macroporous structure, as shown in Figure 1 (c); when the two biomasses are mixed and an appropriate amount of nitrogen source is introduced, a honeycomb porous structure with both micropores and mesopores appears, as shown in Figure 1 (d)(e)(f).
[0093] The samples prepared in all the embodiments and comparative examples of the present invention were subjected to N2 adsorption-desorption experiments using an adsorption instrument, and the specific surface area, pore volume and pore size distribution of the samples were calculated based on the curves. Figure 2 (a) is a schematic diagram of the N2 adsorption-desorption curve detection of all the samples prepared. According to the analysis and calculation of the nitrogen adsorption-desorption curve, the specific surface areas of all the samples are shown in Table 1. From this result, it can be seen that the synergistic effect of the dual biomass carbon source and the nitrogen source melamine is conducive to increasing the specific surface area of the material. As the amount of nitrogen source melamine added increases, the specific surface area begins to decrease, proving that adding too much nitrogen source melamine will block its original pore structure, thereby reducing its specific surface area. This result is consistent with SEM. Figure 2 (b) is a schematic diagram of the pore size distribution detection of all the samples prepared. It can be seen from the figure that the proportion of micropores and mesopores in the dual biomass porous carbon materials of Examples 1 to 3 of the present invention accounts for 85% to 95% of all pores. As shown in the figure, the absorption peaks of RSPC and TAC are relatively low in the range of 1nm to 100nm, indicating that their pores are relatively small. The absorption peak of N-RSPC increases after the introduction of nitrogen source melamine, indicating that the introduction of N doping in biomass carbon materials can increase its pore volume. When the second carbon source tannic acid and nitrogen doping are introduced, the pore volume is greatly increased, and the pore volume of N-RTC-1.5 reaches the maximum value. This is attributed to the synergistic effect of the dual biomass and the appropriate nitrogen and oxygen doping ratio, which greatly increases the specific surface area and porosity of the carbon material due to internal structural defects. It is beneficial to improve the electrochemical properties of the electrode material. The specific surface area and pore size distribution data of all samples are shown in Table 1. It can be seen from Table 1 that the specific surface area and pore volume of the embodiment of the present invention are greater than those of the comparative example.
[0094] Table 1 Specific surface area and pore size distribution data of all samples
[0095]
[0096] Application Example - Electrochemical Performance Analysis
[0097] In order to characterize the electrochemical properties of the carbon materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3, the CHI760E electrochemical workstation produced by Shanghai Chenhua Instrument Co., Ltd. was used for testing. The specific steps are as follows:
[0098] Weigh appropriate amounts of the carbon materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3, grind them in a mortar, and then add conductive agents acetylene black and polyvinylidene fluoride (PVDF) powder. The mass ratio of carbon material, acetylene black, and PVDF is 8:1:1. Add an appropriate amount of N-methyl-2-pyrrolidone to make it into a uniform paste, stir it thoroughly for 4 hours, and evenly load the slurry mixture obtained after stirring on the nickel foam collector. The coating area is 1*1cm 2 , the electrode material load is about 3.5mg. The nickel foam coated with electrode material is placed in a vacuum drying oven, dried at 60℃ for 12h, and finally pressed into electrode sheets with a tablet press. The pressing pressure is 10Mpa and the pressing time is 3min to obtain a working electrode. The electrode sheet prepared above is used as the working electrode of the three-electrode system, the platinum sheet is used as the counter electrode, the Hg / HgO electrode is used as the reference electrode, and the electrolyte is 6M KOH solution. The voltage scanning range of the cyclic voltammetric characteristic curve (CV) is -1.0~0V, and the scanning rate is selected from 5, 10, 20, 30, 40, 50 and 100mV / s. In the constant current charge and discharge curve (GCD) test, the current density is selected from 1, 2, 3, 5, 10 and 20A / g. Figure 3 (a) is the CV curve of RSPC, TAC, N-RSPC, N-RTC-1, N-RTC-1.5 and N-RTC-2 at a scanning speed of 100mV / s. All samples showed distorted rectangles and humps in the potential range of -1V to 0V, indicating that the prepared carbon materials have double-layer capacitance characteristics and pseudocapacitance characteristics generated by the redox reaction of N and O functional groups. N-RTC-1, N-RTC-1.5 and N-RTC-2 showed larger humps and integrated areas, indicating that the dual-biomass porous carbon materials of the embodiments of the present invention have better electrochemical properties and stronger pseudocapacitance. The GCD curves of all electrode materials at a current density of 1A / g are shown in the figure. Figure 3(b) shows that they are all quasi-triangular. It can be seen from the figure that the dual biomass porous carbon materials N-RTC-1, N-RTC-1.5 and N-RTC-2 of the embodiment of the present invention have good Coulomb efficiency and EDLC performance. The GCD curve distortion of N-RTC-1, N-RTC-1.5 and N-RTC-2 can be attributed to the pseudocapacitance induced by the redox activity of N and O functional groups. In addition, the discharge time of N-RTC-1, N-RTC-1.5 and N-RTC-2 is higher than that of N-RSPC, TAC and RSPC obtained in the comparative example, indicating that the dual biomass porous carbon materials of the embodiment of the present invention have stronger adsorption / desorption ability for electrolyte ions, thereby enhancing the capacitance. According to the charge and discharge curve calculation, at each current density, the specific capacitance and capacitance retention rate of all samples are shown in Table 2. It can be seen that the specific capacitance and capacitance retention rate of the dual biomass porous carbon materials N-RTC-1, N-RTC-1.5 and N-RTC-2 of the embodiment of the present invention are higher than those of the samples obtained in the comparative example. Its excellent performance can be attributed to the synergistic effect of ultrahigh specific surface area, layered porous structure and N, O co-doping. In essence, the addition of the second carbon source TA helps to increase the specific surface area. The large specific surface area and layered porous structure provide more active sites and smooth channels for fast ion transfer, while the abundant N and O functional groups improve the electronic conductivity, wettability between electrode and electrolyte, and pseudocapacitive performance.
[0099] Table 2 Specific capacitance data of all samples at different current densities
[0100]
[0101] In order to evaluate the application potential of the dual-biomass porous carbon material of the embodiment of the present invention in supercapacitors, the N-RTC-1.5 obtained in Example 2 was used as an example for the experiment. The specific process is: using 6M KOH as the electrolyte, the two electrodes with the same load mass are assembled into a button-type symmetrical supercapacitor to ensure that the load mass difference of the two symmetrical electrodes is less than 0.0002g. The assembly accessories are assembled in the order of positive electrode shell, spring, gasket, electrode-1, polypropylene diaphragm, electrode-2, gasket, and negative electrode shell; finally, the button-type supercapacitor is packaged on a button battery sealing machine. The voltage scanning range of the cyclic voltammetric characteristic curve (CV) is 0-1V, and the scanning rate is selected from 5, 10, 20, 30, 40, 50 and 100mV / s. In the constant current charge and discharge curve (GCD) test, the current density is selected from 0.5, 1, 2, 3, 5 and 10A / g. A symmetrical supercapacitor device N-RTC-1.5 / / N-RTC-1.5 was produced. Figure 4The electrochemical performance diagram of N-RTC-1.5 in a two-electrode system, where (ab) shows the CV curve of N-RTC-1.5 at a scan rate of 5 to 100 mV / s and the GCD curve at a current density of 0.5 to 10 A / g. The CV curve is a twisted spindle shape, indicating that it has not only a double-layer storage mechanism, but also a pseudocapacitive storage mechanism. When the current density is 1 A / g, the specific capacitance of the N-RTC-1.5 electrode material is 251.8 F / g. Figure 4 (c) is the energy density and power density diagram of N-RTC-1.5 / / N-RTC-1.5 symmetric supercapacitor. It can be seen from the figure that the maximum energy density of N-RTC-1.5 / / N-RTC-1.5 is 18.32Wh / kg, and the maximum power density is 5000W / kg. Figure 4 (d) shows the good cycling performance of the N-RTC-1.5 electrode at a current density of 3A / g. After 10,000 charge and discharge cycles, the capacitance retention rate is 96%, with good cycling stability. In addition, the N-RTC-1.5 / / N-RTC-1.5 device can easily light up a red light-emitting diode, indicating its potential application. The results show that the dual biomass porous carbon material of the embodiment of the present invention is a sustainable high-performance energy storage electrode.
[0102] The supercapacitor electrode material of the present invention is a unique dual-biomass derived nitrogen-oxygen co-doped porous carbon composite material, with reed straw and tannic acid as dual carbon sources, and the synergistic effect of KOH and melamine to construct a unique honeycomb pore structure, which makes the material have a high specific surface area, exposes more active sites, and thus improves the activity of the supercapacitor. The preparation method is simple, the obtained electrode material has a unique structure, and has broad application prospects in the field of energy storage and conversion.
[0103] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A dual biomass porous carbon material, characterized in that: include: The dual biomass carbon source, the activator and the nitrogen source are synthesized in situ under the synergistic effect of the activator and the nitrogen source, with the dual biomass carbon source as the matrix; The dual biomass carbon source includes reed straw and tannic acid, the activator includes potassium hydroxide, and the nitrogen source includes melamine; The dual-biomass porous carbon material is a hierarchical three-dimensional honeycomb structure with both micropores and mesopores. The pore size of the micropores is less than 2nm, the pore size of the mesopores is 2nm to 50nm, the proportion of the micropores and mesopores to all pores is 85% to 95%, and the pore volume is 0.90cm 3 g -1 ~1.30cm 3 g -1 , with a specific surface area of 1900m 2 g -1 ~2600m 2 g -1 The nitrogen doping atomic ratio is 2% to 6%, and the oxygen doping atomic ratio is 12% to 16%.
2. The dual biomass porous carbon material according to claim 1, characterized in that: The mass ratio of the dual biomass carbon source, nitrogen source and activator is 1:1:2.5 to 1:2:3.
5.
3. The method for preparing the dual biomass porous carbon material according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1: heating reed straw and tannic acid for pre-carbonization and cooling them to obtain pre-carbonized reed straw and pre-carbonized tannic acid; S2: mixing the pre-carbonized reed straw, pre-carbonized tannic acid and melamine and grinding them uniformly to obtain a mixed precursor, mixing the mixed precursor with KOH, adding an appropriate amount of deionized water for impregnation, stirring, and drying to obtain a calcined precursor; S3: calcining the calcined precursor at a high temperature in an inert atmosphere to obtain a calcined product, wherein the calcination temperature is 600° C. to 800° C.; S4: acid-washing the calcined product to obtain an acid-washed product; S5: filtering the acid-washed product, washing with deionized water until neutral, and drying to obtain the dual-biomass porous carbon material; In step S2, the mass ratio of the precarbonized reed straw to the precarbonized tannic acid is 1:0.5 to 1:1.5; the mass ratio of the total mass of the precarbonized reed straw and the precarbonized tannic acid, the nitrogen source and the KOH is 1:1:2.5 to 1:2:3.
5.
4. The preparation method according to claim 3, characterized in that: Before step S1, the reed straw is subjected to pretreatment steps of washing, drying, crushing and screening.
5. The preparation method according to claim 3, characterized in that: In step S1, the heating rate of the heating process is 4°C / min to 6°C / min, the pre-carbonization temperature is 400°C to 600°C, and the pre-carbonization time is 0.5h to 1.5h.
6. The preparation method according to claim 3, characterized in that: In step S2, the volume of the deionized water is 20 mL to 30 mL, the stirring time is 11 h to 13 h, the drying temperature is 80° C. to 100° C., and the drying methods include forced air drying and vacuum drying.
7. The preparation method according to claim 3, characterized in that: In step S3, the heating rate is 4°C / min to 6°C / min, and the insulation time is 0.5h to 1.5h.
8. The preparation method according to claim 3, characterized in that: In step S4, the pickling agent used for pickling is HCl solution with a concentration of 1 mol / L to 3 mol / L, and the pickling time is 8 h to 12 h.
9. Use of the dual-biomass porous carbon material according to any one of claims 1 to 2 or the dual-biomass porous carbon material obtained by the preparation method according to any one of claims 3 to 8 in the preparation of supercapacitor electrode materials.
